2020
DOI: 10.1136/annrheumdis-2020-217646
|View full text |Cite
|
Sign up to set email alerts
|

Unique expansion of IL-21+ Tfh and Tph cells under control of ICOS identifies Sjögren’s syndrome with ectopic germinal centres and MALT lymphoma

Abstract: ObjectivesTo explore the relevance of T-follicular-helper (Tfh) and pathogenic peripheral-helper T-cells (Tph) in promoting ectopic lymphoid structures (ELS) and B-cell mucosa-associated lymphoid tissue (MALT) lymphomas (MALT-L) in Sjögren’s syndrome (SS) patients.MethodsSalivary gland (SG) biopsies with matched peripheral blood were collected from four centres across the European Union. Transcriptomic (microarray and quantitative PCR) analysis, FACS T-cell immunophenotyping with intracellular cytokine detecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
106
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 113 publications
(112 citation statements)
references
References 47 publications
6
106
0
Order By: Relevance
“…Our results regarding activated Tfh in pSS are consistent with previous studies that have shown an expansion of circulating activated Tfh in patients with pSS, 16 17 mostly in those with extraglandular manifestations and/or high disease activity 7 8 and a correlation between activated Tfh and disease activity. 9 10 On the opposite, in another study, pSS patients had a normal frequency of blood activated Tfh, but an increased level of T follicular regulatory (Tfr) cells and blood Tfr/Tfh ratio.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our results regarding activated Tfh in pSS are consistent with previous studies that have shown an expansion of circulating activated Tfh in patients with pSS, 16 17 mostly in those with extraglandular manifestations and/or high disease activity 7 8 and a correlation between activated Tfh and disease activity. 9 10 On the opposite, in another study, pSS patients had a normal frequency of blood activated Tfh, but an increased level of T follicular regulatory (Tfr) cells and blood Tfr/Tfh ratio.…”
Section: Discussionsupporting
confidence: 92%
“…Indeed, Tph have now been studied in many auto-immune diseases, such as systemic erythematosus lupus, systemic sclerosis or rheumatoid arthritis, 18–20 but only few data are available in pSS. 16 17 We confirmed their expansion in the blood of pSS patients and our study is one of the first to describe their association with clinical and biological characteristics.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…CD4 + CXCR5 + ICOS + Tfh cells were mildly induced by stimulation dynabeads ® human T-activator CD3/ CD28, and there was a statistically significant increase after the addition of exogenous IL-12 and/or IL-21 (Figures 4A, D). This data is in line with findings that IL-12 and IL-21 are important in differentiation and generation of Tfh cells (19)(20)(21). As expected, exogenous IL-17 has no effect on differentiation of Tfh cells (Figures 4A, D).…”
Section: Tfh Cells Induction By Soluble Factor In the Serum Of Hbv-acsupporting
confidence: 93%
“…Moreover, higher fractions of ICOS(+) Tfh cells were observed, and a positive association was found between autoantibody levels and increased level of Tfh cells in pSS compared to controls (Brokstad et al, 2018). Recent research also highlighted Tfh and pathogenic peripheral-helper T-cells (Tph), IL-21, and the ICOS costimulatory pathway as key pathogenic players in SS immunopathology (Pontarini et al, 2020). In addition, low IFN-γ levels and indifferent expression levels of other factors (IL-6, IL-4, and TGFβ1) were found in ELISA, and this controversial finding may be explained by low disease activity in our pSS patients (Karabulut et al, 2018).…”
Section: Discussionmentioning
confidence: 95%